"It's the truth about women— that we get lost": Andrea Dworkin, public memory, and archival resilience. Issue 3 (3rd July 2022) - Palmer-Mehta, Valerie
ABSTRACT: Few figures vivify the struggle over public memory and survival as compellingly as second wave feminist Andrea Dworkin, who was a visionary and gadfly within the movement. This analysis provides an interior view of this public and often misunderstood figure as it advances a theory of archival resilience. Acting as a historical corrective, archival resilience emboldens the marginalized to interrupt the cohesive hegemonic imaginary to which they have been subjected and be active agents in producing a parallel historico-political reality through the preservation of records that center their voices and experiences on their own terms. Following Dworkin, archival resilience creates a record of marginalized lives through the 1) strategic, defiant act of valuing the self and one's community in the service of record preservation despite a hostile, disconfirming culture; 2) documentation of the multifaceted nature of survival and survival strategies used by the marginalized to illuminate the precarity of their lives; and 3) rejection of celebratory or politically "respectable" representations in favor of preserving the full picture of people and movements, even those aspects that are stigmatized or anti-heroic. Archival resilience creates a record of marginalized lives so that we can gain an appreciation of their struggle, worth, and value.